Diagnosis and Management of Large Artery Atherosclerosis. Issue 2 (April 2023) - Chaturvedi, Seemant
ABSTRACT: OBJECTIVE: Ischemic stroke due to large vessel atherosclerosis is a significant cause of stroke globally. With the aging population, the number of people with atherosclerotic stroke will increase in the coming decades. This article reviews the recent developments in the assessment and treatment of extracranial and intracranial atherosclerotic disease. LATEST DEVELOPMENTS: More intensive dual antiplatelet therapy can now be recommended for patients with transient ischemic attack or stroke. More stringent blood pressure and lipid control is also advised. The need for carotid revascularization will likely decrease in the coming decades because of advances in multimodal medical therapy; in particular, the role of revascularization for treating asymptomatic carotid stenosis is controversial. Patients with symptomatic intracranial stenosis should receive intensive medical therapy. Interest in high-resolution carotid plaque imaging is growing. ESSENTIAL POINTS: The prevention of stroke due to large vessel atherosclerosis has improved owing to advances in medical therapies. The role of carotid revascularization is unclear for many patient subgroups.